OPINI MASYARAKAT BATAK PADA PROGRAM ACARA HORAS DI RANTAU PADA RTV (Studi Kasus Di Kelurahan Tanjung Rhu Kecamatan Lima Puluh Kota Pekanbaru) - Siburian, Joi; Tinambunan, W. E. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Program is one means of communication to influence the audience. The number of program aired on television show that make the audience think watching what message content delivered in each program of the event. Overseas program Horas in a Batak music program, the program is packed with interesting events that can affect the audience and making the changes. This study aims to determine public opinion on the Batak in Rantau Horas Program on Rtv in the Village District of Tanjung Rhu Fifty Pekanbaru City and the factors that Influence the formation of public opinion Village Subdisrict Tanjung Rhu Fifty Pekanbaru City.This study uses descriptive qualitative data collection techniques of observation, interviews, and dokumentansi. The data obtained is then processed to be reduced, resulting presented to a general conclusion. Informants in this study amounted to 12 based on snowball sampling method that researchers use. While for checking the validity of the data the researcher used triangulation techniques and extension participation.The results showed that public opinion Batak village of Tanjung Rhu Fifty Pekanbaru City District of the program event at Rantau Horas is very interesting, because it has educational value that can increase knowledge and positive learning to watch. Factors that influence the formation of public opinion Batak, because that show is very entertaining program and describe social reality in the city of Pekanbaru.Keywords: Public Opinion, Horas di Rantau, Program Events